Metagenomic Sequencing Combined with Metabolomics to Explore Gut Microbiota and Metabolic Changes in Mice with Acute Myocardial Infarction and the Potential Mechanism of Allicin - Gao Y; Qin G; Liang S; Yin J; Wang B; Jiang H; Liu M; Luo F; Li X (Drug Design, Development and Therapy)
Yijie Gao,1 Gaofeng Qin,2 Shichao Liang,3 Jiajie Yin,4 Baofu Wang,1 Hong Jiang,1 Mengru Liu,1 Fangyuan Luo,3 Xianlun Li1 1National Integrated Traditional and Western Medicine Center for Cardiovascular Disease, China-Japan Friendship Hospital, Beijing, People’s Republic of China; 2Department of Traditional Chinese Medicine, Binzhou Medical University Hospital, Shandong, People’s Republic of China; 3China-Japan Friendship Hospital, Chinese Academy of Medical Sciences and Peking Union Medical College, Beijing, People’s Republic of China; 4Institute of Clinical Medical Sciences, China-Japan Friendship Hospital, Beijing, People’s Republic of ChinaCorrespondence: Xianlun Li, Email leexianlun@163.comBackground: Acute myocardial infarction (AMI) is a significant contributor to global morbidity and mortality. Allicin exhibits promising therapeutic potential in AMI as a primary bioactive component derived from garlic; however, its underlying mechanisms remain incompletely elucidated.Methods: Our study induced AMI in mice by ligating the left coronary artery, and administered allicin orally for 28 days. The cardioprotective effects of allicin treatment were comprehensively assessed using echocardiography, histopathological examinations, intestinal barrier function, and serum inflammatory factors. The potential mechanisms of allicin were elucidated through analysis of metagenomics and serum metabolomics. Network pharmacology (NP) was used to further investigate and validate the possible molecular mechanisms of allicin.Results: Our findings revealed allicin’s capacity to ameliorate cardiac impairments, improve intestinal barrier integrity, and reduce serum IL-18 and IL-1β levels after AMI. Further analysis demonstrated that the administration of allicin has the potential to ameliorate intestinal flora disorder following AMI by modulating the abundance of beneficial bacteria, such as g_Lactobacillus, g_Prevotella, g_Alistipes, and g_Limosilactobacillus, while reducing the abundance of harmful bacteria g_Parasutterella. Additionally, it exhibits the ability to enhance myocardial energy metabolism flexibility through modulating metabolites and key enzymes associated with the fatty acid metabolic pathway. Mechanistically, NP and in vivo experiments indicated that allicin might suppress pyroptosis and reduce inflammatory response via blocked activation of the NF-κB-mediated NLRP3/Caspase-1/GSDMD pathway. Moreover, Spearman correlation analysis suggested a significant association between the allicin-induced alterations in microbiota and metabolites with cardiac function and inflammatory cytokines.Conclusion: Our study demonstrated that allicin alleviated myocardial injury and reduced inflammatory response by inhibiting the NF-κB-mediated NLRP3/Caspase-1/GSDMD pathway while remodeling microbiota disturbance, improving serum metabolic disorder, and enhancing the intestinal barrier. These research findings offer a novel perspective on the potential therapeutic value of allicin as an adjunctive dietary supplement to conventional treatments for AMI. Keywords: acute myocardial infarction, allicin, gut microbiota, metabolomics, intestinal barrier, pyroptosis